PERILAKU HIDUP BERSIHDAN SEHAT MASYARAKAT PEMUKIMAN KUMUH ( SLUM AREA ) DI KELURAHAN TELUK BINJAI KECAMATAN DUMAI TIMUR KOTA DUMAI - Devi Asmara; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Health is a state of well-being of body, mind and social life that allow people to live socially and economically productive. To achieve a healthy principle, services (MOH) has established 10 indicators of healthy living a clean and healthy behaviors. We shall run, at least 65% of people in the region who are capable of running PHBs as a pilot area to implement PHBs. The purpose of this study was to determine whether people in Teluk Binjai Village area is already running 8 of 10 indicators of clean and healthy behaviors are set by the government. The factors - factors that affect PHBs is knowledge, income and employment. Village of Binjai bay is one of the villages in Dumai City slums are still vulnerable to flood and dengue fever (DHF). Where 12 of the 20 RT RT classified as slums. This is because the population density is increasing and making the area in Teluk Binjai Village is classified as slums. The target is expected to run a clean and healthy life behavior, namely, the healthy behavior if the community can run PHBs above 50%, less healthy behaviors between 10-50% PHBs and unhealthy behaviors between 10-30% PHBs. Dumai city health department, noting that the District of East Dumai flood-prone areas and dengue fever (DHF) from 9 Village in Kota Dumai most disease dengue fever (DBD) accounted for approximately 32.07% 85 people are in the Bay Village area Binjai. This is the case because there are many people in the area who do not run a clean and healthy lifebehavior.Keywords: Indicators of PHBs, health, hygiene, factors affecting